(untitled) (The Eurasia Proceedings of Educational and Social Sciences, 2019)
This study aims to reveal the opinions of middle school students regarding science after attending “Artvin Bilim ve Robotikle Renkleniyor” project including variety of science activities related with robotic, science and nature under the scope of TÜBİTAK 4004 Nature and Science School program. Data of the current study was collected via a personal information form and a survey from a total of 30 6th and 7th grade students in six middle schools in Artvin province who participated in the project. In this study, a two-question survey developed by Akay (2013) was used to reveal the students’ opinion regarding science. Qualitative data of the study were analyzed by using content analysis method and quantitative data were analyzed by giving frequency and percentages. 19 of the students are female and 11 are male. 14 of these students are in 6th grade and 16 of them are in 7th grade. At the end of the project, students were asked to define science and the students were asked what would you like to invent if you were a scientist. Moreover, researchers tried to determine how the students’ attitudes towards science changed after the project. When the respond of the students were examined, it is seen that most of the students define science as the work of producing new things, discovering and explaining the universe. In addition, the students stated that they want to build a time machine that facilitates transportation if they were a scientist. Furthermore, the number of students who want to discover a flying car and teleportation tool is higher than others. In general, it is seen that most of the student want to discover transport and technology related products. Most of the student state that their science interest has increased after the Project. Moreover, the number of students who realize the importance of science and increase their curiosity and desire to learn is also high. So, it can be said that the project has increased students’ positive perceptions towards science.